Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing Pada UMKM Es Teh Solo Cabang Cidodol - Setiawati, Erika Sabilla Atta; Eka Helmalia, Dea; Luthpiyatunnisa, Luthpiyatunnisa; Tamara, Meri; Lestari, Tri (CV Warnak Johanna Nusantara, 2025)
Most MSME actors still use simple methods in calculating the cost of production (HPP), resulting in a high potential for inaccuracies in determining costs and selling prices. UMKM Es Teh Solo Branch Cidodol is an example of a business that has not fully implemented cost accounting methods. The purpose of this research is to analyze the application of the full costing method in calculating the cost of production (HPP) at UMKM Es Teh Solo Branch Cidodol. This research employs a qualitative approach, where data is collected through interviews and documentation. The findings indicate that there is a difference between the HPP calculation according to the business owner and the calculation based on the full costing method. The HPP according to the owner is IDR 2,911 per cup, while based on the full costing method it is IDR 2,941 per cup. This difference is caused by variations in the grouping and recording of costs, where the full costing method includes all components of costs comprehensively, such as raw material costs, direct labor, fixed overhead, and variable overhead. Thus, the more accurate calculation results can be demonstrated through the full costing method and can serve as a stronger basis for business decision-making and pricing